CLINICAL SPECTRUM AND IMMUNOLOGICAL PROFILE OF PATIENTS WITH MIXED CONNECTIVE TISSUE DISEASE PRESENTING IN A TERTIARY CARE HOSPITAL - ASIF , S; JAVED, S; HUSSAIN , A; KHAWAJA, MA; KHOKHAR, HS; HAROON, M; ZAHOOR, S (Biological and Clinical Sciences Research Journal, 2022)
This study investigated the clinical spectrum and immunological profile of mixed connective tissue disease (MCTD) patients in a tertiary care hospital in Pakistan. This study was conducted in the Department of Rheumatology at Fatima Memorial Hospital in Lahore for six months from March to August 2021. A clinical diagnosis was made based on the Kasukawa criteria. In this study, 45 patients who fulfilled the MCTD criteria were enrolled. Their clinical presentation and laboratory findings were studied, and disease characteristics and demographics were recorded using a self-designed proforma. The analysis of the collected data was done using SPSS version 25.0. Of 45 patients, 42 were females, and 3 were males, with a mean age of 33. The most common clinical features studied were Raynaud phenomenon (found in 36 (80%) patients), sclerodactyly (in 12 (26.7%) patients), digital ulcers (in 12 (26.7%) patients), puffy hands (in 14 (31.1%) patients), skin tightness (in 21 (46.7%) patients), oral ulcers (in 8 (29.6%) patients), rash over face (in 13(28.9%) patients), rash over other areas than face (in 16 (35.6%) patients), calcinosis (in 2(4.4%) patients), diffuse hair loss (in 10(37%) patients), arthritis (in 21(46.7%) patients), proximal muscle weakness (in 9 (20%) patients), dryness of eyes and mouth (in 13 (48.1%) patients), and esophageal dysmotility (in 9 (20%) patients). Pulmonary HTN was found in 5(11.1%) patients, ILD with NSIP pattern in 7(13.7%) patients, and UIP pattern on HRCT chest was found in 2(4.4%) patients. Several antibodies were found in patients, including U1RNP in 24(53.3%) patients, ANA in 33(73.3%) patients, AntiScl 70 in 9(20%) patients, Anti-centromere in 2(4.4%) patients, Anti jo1 in 1(3.7%) patient, Anti-dsDNA in 14(31.1%) patients, LAC in 1(3.7%) patient, ACL in 1(3.7%) patient, Anti Ro in 14 (31.1%) patients, and Anti La in 2 (7.4%) patients. S/CPK was raised in 10(22.2%) patients. MCTD is an immune-mediated disorder affecting multiple systemic organs with shared features of three autoimmune disorders: scleroderma, systemic lupus erythematosus (SLE), and polymyositis. Sometimes, it can convert to a full autoimmune rheumatological condition, so if it is treated early, future complications can be prevented. Autoimmune rheumatological condition, so if it is treated early, future complications can be prevented.